PENERAPAN MODEL TEAM GAME TURNAMENT (TGT) UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN RESPON SISWA KELAS VII SMP NEGERI 6 KOTA BENGKULU - Wati, Andi Mutiara; Herawaty, Dewi; Rahimah, Dewi (JP2MS, 2018)
The research aims to find out how to application’s Co-operative Learning Team Games Turnamen assisted in order to improve activity and study’s result on the material of  This study aims to find out how to apply cooperative learning model TGT type so that there is increasing activity and student response on the matter of integers and fractions. The type of research conducted is Classroom Action Research (PTK) with collection techniques through student activity observation sheet, test of mathematics learning result and student response. Student activity is enhanced by appropriate group sharing, providing learning guidance to low-ability students, giving admonitions and actions to students who do not follow the learning activities well. Increased student activity can be seen from the average score from cycle I to cycle III that is: 18,63; 21,38; 26,13. Student response is enhanced by guiding students to be more interested and enthusiastic in learning, as well as learning motivation in the form of game that is game turnament. Increased student response to the application of TGT learning model seen from the average score of student response questionnaire from cycle I to Cycle III that is: 35,3; 43.25; 65 Keywords: Activity,Response,Team Game Turnament